2016
DOI: 10.22499/3.6601.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the AWAP daily precipitation spatial analysis with an independent gauge network in the Snowy Mountains

Abstract: The Bureau of Meteorology's Australian Water Availability Project (AWAP) daily precipitation analysis provides high resolution rainfall data by interpolating rainfall gauge data, but when evaluated against a spatially dense independent gauge network in the Snowy Mountains large systematic biases are identified. Direct comparisons with the gauge data in May-September between 2007 and 2014 reveal average root mean square errors of about 4.5 mm, which is slightly greater than the average daily precipitation amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Developing gridding precipitation indices from daily precipitation observations is not forthright since averaging daily precipitation information from numerous stations and interpolating it into gridded precipitation data dampens the extremes and misrepresents the spatial and temporal variability that exists in the original station data 5 . If the rain gauges are extremely sparse, acquiring a correct distribution of rainfall through interpolation is even more difficult and the low density of precipitation stations leads to significant uncertainties, especially in regions where the rainfall varies significantly in space and time [32][33][34] . Comparing to conventional interpolation method, the ANUSPLIN show its priority in modelling the precipitation under complex terrain and data-scarce condition.…”
Section: Discussionmentioning
confidence: 99%
“…Developing gridding precipitation indices from daily precipitation observations is not forthright since averaging daily precipitation information from numerous stations and interpolating it into gridded precipitation data dampens the extremes and misrepresents the spatial and temporal variability that exists in the original station data 5 . If the rain gauges are extremely sparse, acquiring a correct distribution of rainfall through interpolation is even more difficult and the low density of precipitation stations leads to significant uncertainties, especially in regions where the rainfall varies significantly in space and time [32][33][34] . Comparing to conventional interpolation method, the ANUSPLIN show its priority in modelling the precipitation under complex terrain and data-scarce condition.…”
Section: Discussionmentioning
confidence: 99%
“…The errors are larger at high elevations (SY and TA) where gauges are fewer, and when there is frozen precipitation, and/or topography is exposed to prevailing winds (Chubb et al, 2016).…”
Section: Comparison With Daily Rainfall Analysismentioning
confidence: 99%
“…This daily adjustment does not directly account for any orographic mechanisms that may enhance/redistribute precipitation, rather it is assumed that such processes are observed by the surface network. Chubb et al (2016) employed an independent network of surface observations over the Snowy Mountains of southeast Australia to identify biases in the AWAP precipitation product arising from the orography. Focussing on wintertime precipitation, they found that the AWAP precipitation strongly underestimated precipitation by up to 50% on the immediate upwind (westerly) slope of the Snowy Mountains, while weakly overestimated downwind precipitation by 10-20%.…”
Section: Discussionmentioning
confidence: 99%
“…The verification scores described in this section are obtained from Ebert (2008) and have commonly been used to evaluate precipitation forecasts (e.g. Johnson et al 2013;Chubb et al 2016). The AWAP daily precipitation, which is produced from surface precipitation observations, is defined as the "ground truth" to evaluate the ACCESS-VT precipitation forecasts.…”
Section: Analysis Methods -Verification Scoresmentioning
confidence: 99%